Biofumigation with Brassica spp for the control of cylindrocarpon black foot disease of grapevines - Bleach, C.M.; Jones, E.E.; Jaspers, M.V. (New Zealand Plant Protection, 2009)
Green crops of Brassica species incorporated into the soil release volatile isothiocyanates which are known to suppress pathogenic fungal species Firstly crops of mustard (Brassica juncea) rape (B napus) and oats (Avena sativa) were grown for 5 weeks in a vineyard site previously infested with Cylindrocarpon spp The crops were cultivated into the soil and the area covered with polythene After 2 weeks callused cuttings of rootstock 101104 and 5C were grown for 9 months and infection assessed Disease incidence in rootstocks 10114 and 5C was reduced in the mustard treatment by 11 and 43 respectively The following year the site was inoculated with Cylindrocarpon spp grown on wheat grains The second experiment used three mustard treatments mustard meal cultivated into the soil (Trt 1) mustard grown once to flowering with cultivation (Trt 2) and mustard grown twice to flowering with cultivation each time (Trt 3) In rootstock 5C disease incidence was reduced in all treatments by more that 41 and in rootstock 10114 disease incidence was reduced in Trt 1 and 3 by 30 and 18 respectively These findings suggest that biofumigation using mustard may be a highly effective method for the control of Cylindrocarpon black foot disease